Unpacking the resource impacts of digitally-mediated domestic practices using resource trace interviewing. Issue 3 (3rd July 2022) - Friday, Adrian; Hazas, Mike; Bates, Oliver; Morley, Janine; Lord, Carolynne; Widdicks, Kelly; Gormally-Sutton, Alexandra; Clear, Adrian
ABSTRACT: The home has been the subject of investigation in the social sciences and interaction design communities for decades. This has been driven not least by a wish to understand technology, energy demand, and how it might be understood in terms of social practices. In this paper, we reflect on several studies that have sought to capture this relationship. We introduce an evolving methodological approach we term 'Resource Trace Interviewing' that extends interview practice using visualizations of fine-grained quantitative data from sensors and software deployed in the home. By facilitating fuller accounts and joint sense-making between participants and researchers, this method better reveals the patterns of technology and energy use in the digitally connected home, and how this in turn relates to domestic practices. We reflect, for the first time, on the strengths and limitations of this approach as a guide to others studying similar socio-technical settings.